2020
DOI: 10.1177/1533033820928073
|View full text |Cite
|
Sign up to set email alerts
|

Sodium Tanshinone IIA Sulfonate Attenuates Tumor Oxidative Stress and Promotes Apoptosis in an Intermittent Hypoxia Mouse Model

Abstract: Objective: Intermittent hypoxia, a significant feature of obstructive sleep apnea, has pro-tumorigenic effects. Here, we investigated the effect of sodium tanshinone IIA sulfonate on oxidative stress and apoptosis in a mouse model of Lewis lung carcinoma with intermittent hypoxia. Methods: Mice were randomly assigned to normoxia (control), normoxia plus sodium tanshinone IIA sulfonate (control + sodium tanshinone IIA sulfonate), intermittent hypoxia, and intermittent hypoxia + sodium tanshinone IIA sulfonate g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…According to the IH exposure, TSA administration, miR-138 agomir, and antagomir injection, the animals were randomized as CTL, IH, IH + TSA, IH + TSA + miR-138 mimic, and IH + miR-138 inhibitor groups. Under IH conditions, mice were placed in a chamber, with oxygen content altering from 21% to nadir 6%–8% within 120 s for an 8-h period every daytime for 5 weeks consecutively, as mentioned previously [ 6 ]. During the experiment, animals were kept in standard cages with the 12-h/12-h high-dark cycle, with free access to food and water.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…According to the IH exposure, TSA administration, miR-138 agomir, and antagomir injection, the animals were randomized as CTL, IH, IH + TSA, IH + TSA + miR-138 mimic, and IH + miR-138 inhibitor groups. Under IH conditions, mice were placed in a chamber, with oxygen content altering from 21% to nadir 6%–8% within 120 s for an 8-h period every daytime for 5 weeks consecutively, as mentioned previously [ 6 ]. During the experiment, animals were kept in standard cages with the 12-h/12-h high-dark cycle, with free access to food and water.…”
Section: Methodsmentioning
confidence: 99%
“…At 1-week post-IH exposure, mice were subcutaneously injected with LLC cells (1 × 10 6 /100 μL of PBS) in the right flank. After the tumor grew to an appropriate volume (around 5–7 days post-LLC administration), TSA (10 mg/kg) was administered to the animals in IH + TSA and IH + TSA + miR-138 inhibitor groups daily through intraperitoneal injection [ 6 ]. Mice in the IH + TSA + miR-138 inhibitor group received miR-138 antagomir intratumoral injection (25 nmol diluted in 100 μL of PBS per mouse), whereas those in the IH + miR-138 mimic group received miR-138 agomir injection (25 nmol per mouse).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, TanIIA reduced oxidative stress in the serum of tumor-bearing mice by combining intermittent hypoxia. TanIIA promotes apoptosis of tumor cells, which may be related to the activation of Nrf2 [ 65 ]. Similar protective effects were also observed in mice with experimental pancreatitis [ 66 ].…”
Section: Mechanism Of Action Of Taniia In Tissue Inflammation and Fib...mentioning
confidence: 99%
“…On this basis, we have derived a series of chemical compounds. Among them, TB3 was obtained by introducing the aromatic ring fragment at the benzyl position of the furan ring ( 16 ). It was found that the novel tanshinone analog, TB3, significantly inhibits the proliferation and cell cycle of PCa cells, and has lower cytotoxicity to human normal liver than other tanshinone analogs.…”
mentioning
confidence: 99%